MODEL RLB TURUNAN NAFTAKUINON INHIBITOR SEL LINE HELA - Samsul Hadi; Uripto Trisno Santoso; Muhammad Luthfi Firdaus (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Cervical cancer is a disease that is dangerous for life. Naphtaquinone is an anticancer agent whose derivatives have been successfully synthesized, so it is necessary to study QSAR to evaluate its potency. The purpose of this study was to determine the molecular descriptors of naphtoquinone-derived compounds that have a significant effect on the anticancer activity of HeLa cells and compile them into a valid QSAR model. A total of 15 compounds from naphtoquinone derivatives were used for modeling. The descriptors that were tried included 1,863 topological descriptors and physico-chemical properties descriptors. Results of correlation analysis obtained 17 descriptors that are feasible to be tested in modeling. Results of backward method obtained 3 descriptors that have a significant effect, namely AATSC6Z, AATSC7m, and MAXaaCH. The MLR model based on 3 descriptors fulfills the goodness of fit requirements with R=0.873, R2=0.763, R 2 Adjusted=0.698, F value=0.0009 (Ftable=11.778). The results of the validation test using the CV-LOO method obtained a value of Q2=0.572 and CV-LMO obtained a value of Q2=0.518 so that this HKSA model can be stated as a valid HKSA model.